Efektivitas Pembelajaran Daring Pada Mata Kuliah Kemahiran Berbicara Bahasa Arab di Universitas Alazhar Indonesia - Rahmah, Ghina Kania (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study discusses the level of effectiveness of online methods in the learning process of Arabic speaking proficiency courses during covid-19 spread in Indonesia at the University of Alazhar Indonesia. This research, refers to how the students batch 2019 respond to online learning in this Arabic speaking proficiency course.Online lectures in this modern era are related to the use of technological media, from the internet or other applications such as Zoom, WhatsApp and other. In the context of Arabic, speaking proficiency is a mandatory skill that students must master and is one of the final goals of foreign language learning in order to gain the ability to express thoughts in the form of ideas, and courage in communicating with interlocutors using Arabic. The purpose of this study was to determine the effect of online learning on the Arabic speaking proficiency course on the learning outcomes of Arabic speaking proficiency for Arabic Literature Students at Al Azhar University Indonesia. As for the method used in this study, the author uses the Pearson Correlation method with the pieosary technique. The effectiveness of online learning in the Arabic speaking proficiency course at the University of Alazhar Indonesia has a good enough effect on increasing understanding in learning in Arabic speaking proficiency courses. they are also greatly helped by the use of available communication aids